KEAMANAN CITRA DIGITAL DENGAN MEMANFAATKAN PROSES PENERAPAN ALGORITMA DATA ENCRYPTION STANDART (DES) PADA EKTRAKSI PIXEL - Achmad Fauzi; Rizka Putri Rahayu (Jurnal Informatika Kaputama (JIK), 2020)
In today's digital technology, almost all activities can be documented in the form of digital images. The problem that arises is that images that are confidential can be stolen and accessed by people who are not entitled. To overcome this security problem, image files can be encrypted using cryptographic algorithms. One cryptographic algorithm that can be used is the Data Encryption Standard (DES) algorithm. This algorithm is a block cipher with a size of 64 bits or 8 bytes. Therefore, DES is used to encrypt image files per 8 bytes. Each encryption process will pass 16 cycles and produce cipher bytes. The result of encryption is an image file with an unrecognized format and cannot be opened because the contents of the byte file have been randomized. To return the scrambled file back to the original image file, perform the decryption process using the same key as the encryption key. The application can be used to encrypt and decrypt images using the DES algorithm. The application can also display the steps of the encryption and decryption process towards the contents of the byte in the file.